Shoulder joint position sense improves with elevation angle in a novel, unconstrained task - Suprak, David N.; Osternig, Louis R.; van Donkelaar, Paul; Karduna, Andrew R. (Journal of orthopaedic research, 2006)
Proprioception, encompassing the submodalities of kinesthesia and joint position sense, is important in the maintenance of joint stability, especially in the shoulder. The purpose of this study was to examine the effects of plane and elevation angle on unconstrained shoulder joint position sense. Twenty‐two subjects (12 male, 10 female) without a history of shoulder pathology were recruited from a university campus. Subjects attempted to replicate, with respect to plane and elevation angles, various target positions. Target positions consisted of five plane angles at 90° of arm elevation and five arm elevation angles in the scapular plane. All target positions were tested twice to assess the reliability of the measurement. Intraclass correlation coefficients were generally low across target positions, possibly owing to the novelty and demanding nature of the task. No differences in repositioning errors were observed between plane angles (p = 0.255). Repositioning errors decreased linearly as the elevation angle increased from 30° to 90° (p = 0.007) and increased again from 90° to 110° of elevation (p = 0.029). Our results suggest that unconstrained joint position sense may be enhanced with increased muscular activation levels. Further, afferent feedback from musculotendinous mechanoreceptors may dominate over that from capsuloligamentous sources in unconstrained movements. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 24:559–568, 2006